Training on Preparing Technology-Based Financial Reports and Tax Filling for MSMEs at Samirono Area - Omenu, Roberto B. T.; Paramitalaksmi, Ratri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service aims to improve the ability of MSMEs to prepare financial reports and tax fillings through the use of application technology. The program was carried out on two MSME partners located in the Samirono area, Sleman, DI Yogyakarta. The program implementation was carried out through observation, socialization, training, and evaluation methods. This activity lasted for 1.5 months for a total of 6 visits individually for each partner. The results of the service showed a significant increase in partners' ability to operate the Akuntasiku bookkeeping application for financial reporting and partners' understanding of the calculation of MSME Final Income Tax, NPWP ownership, and how to report the Annual Tax Return, which has implications for more professional and sustainable business management and tax compliance.